2020
DOI: 10.1038/s41598-020-59347-y
|View full text |Cite
|
Sign up to set email alerts
|

Sperm enrichment from poor semen samples by double density gradient centrifugation in combination with swim-up for IVF cycles

Abstract: Sperm preparation in iVf cycles using density gradient centrifugation (DGc) in combination with swim-up (SU) has been widely adopted in reproductive centres worldwide. it is a fact that the sperm recovery rate following one DGc from poor semen samples (showing liquefaction defects/containing too many unresolvable clots or rare sperm) is relatively low. our results showed that double DGc (DDGC) is effective at increasing the sperm recovery rate from poor semen samples. However, DDGC may increase the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…After oocytes retrieval, insemination was performed by the conventional IVF or ICSI method in IVF-plus medium (Vitrolife, Sweden). The observation of pronuclei, embryo culture and score were performed as we described previously 24 . Briefly, 18 h after insemination, zygotic embryos (day 1) with 2 pronuclei were considered normal fertilization and were placed into G1 plus medium (Vitrolife, Sweden) for further culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After oocytes retrieval, insemination was performed by the conventional IVF or ICSI method in IVF-plus medium (Vitrolife, Sweden). The observation of pronuclei, embryo culture and score were performed as we described previously 24 . Briefly, 18 h after insemination, zygotic embryos (day 1) with 2 pronuclei were considered normal fertilization and were placed into G1 plus medium (Vitrolife, Sweden) for further culture.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 18 h after insemination, zygotic embryos (day 1) with 2 pronuclei were considered normal fertilization and were placed into G1 plus medium (Vitrolife, Sweden) for further culture. On day 3, the morphology of the embryos was evaluated and scored according to a previously described method 24 . Grade I and II embryos were taken as top embryos, while Grade III embryos were taken as non-top embryos.…”
Section: Methodsmentioning
confidence: 99%
“…Sperm preparation techniques have previously been evaluated without reaching a firm consensus. 19,[21][22][23][24][25][26][27][28][29] Several reasons could explain the discrepancies between the published reports such as the number and types of techniques being compared (eg, density gradient, semen and/or pellet swim-up, double density gradient or density gradient followed by swim-up), the included participants (eg, fertile and/ or infertile men), the sample size, and the measured outcomes (eg, sperm DNA fragmentation, embryo development or pregnancy rates).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Previous studies found that SARS, 1 of the 3 epidemic coronaviruses to emerge in the past 20 years and that shows similar clinical presentations to COVID-19, 18 could cause orchitis 19 and focal testicular atrophy. 20 Considering the tens of millions of COVID-19 cases and that men are more vulnerable to COVID-19 than women, [21][22][23] it is imperative to determine the effect of COVID-19 on male reproduction. 24 Several studies have been performed on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation